Inovasi Pengelolaan Zakat Profesi dan Pengaruhnya terhadap Minat Berzakat di Dompet Dhuafa Waspada - Juliana Nasution (J-EBIS (Jurnal Ekonomi dan Bisnis Islam), 2019)
Zakat’s fund raising is currently far below its great potential in Indonesia which indicates the low of interest from the community to tithe. To increase the interest, the organization of Zakat Management created someinnovations to the management of zakat. This study aims to determine the innovations of zakat management which have been initiated by Dompet Dhuafa Waspada and to see how it affects the interest of tithe to Dompet Dhuafa. The sample are Professional Muzakki who pay zakat at LAZ Dompet Dhuafa Waspada. This study was a quantitative study, used data processing methods through SPSS 22. The results of the study showed that Dompet Dhuafa Waspada has made some innovations of collecting zakat method, its distribution program, its utilization and reporting system on management implementation. While the impact analysis found that the innovations of zakat management variables aff ected the variable interest to tithe with t count> t-table is 52.339> 1.66.